2018
DOI: 10.25271/2018.6.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility Pattern of Pathogenic Bacteria Causing Urinary Tract Infections at Azadi Hospital In Duhok City\Kurdistan Region of Iraq

Abstract: Urinary tract infections represents one of the most common diseases encountered in medical practice affecting people of all ages from the neonate to the geriatric age group. The aim of this study was to determine and evaluate the antimicrobial susceptibility patterns for most common strains of bacterial urine isolates taken from patients at Azadi teaching hospital laboratories in Duhok city/Kurdistan region in Iraq, for two years (2014 and 2015). A retrospective survey study was conducted and 1003 data of urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…E. coli has also been found to be the most common cause of UTIs in males, according to other studies (32,33). E. coli was shown to be the most frequent bacteria responsible for urinary tract infections (UTIs) in earlier research done in Iraq (7,34). This study's findings are in line with those of an earlier Iranian investigation that identified P. aeruginosa as the second most prevalent gram-negative cause of UTI in human (35).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…E. coli has also been found to be the most common cause of UTIs in males, according to other studies (32,33). E. coli was shown to be the most frequent bacteria responsible for urinary tract infections (UTIs) in earlier research done in Iraq (7,34). This study's findings are in line with those of an earlier Iranian investigation that identified P. aeruginosa as the second most prevalent gram-negative cause of UTI in human (35).…”
Section: Resultssupporting
confidence: 87%
“…According to recent studies in Iraq, the three most frequent pathogens responsible for UTIs, E. coli, Staphylococcus spp. and K. pneumonia, are all antibiotic-resistant (6,7). Urinary tract infections (UTI) that are diagnosed and treated early are less likely to result in morbidity (8).…”
Section: Introductionmentioning
confidence: 99%
“…aureus was the most predominant gram-positive species isolated from all UTI cases with a total number of 50/380 (13.15%). Inside Iraq, the current results agreed with [16,17] who recorded both of them (11%) and [18] whom recorded (14.29%) for Staph. aureus.…”
Section: Isolation Of Staph Aureussupporting
confidence: 89%
“…Likewise, other studies reported that E. coli was the most common pathogen causing UTIs in males (17,18). Likewise, several previous studies conducted in Iraq showed that E. coli was the most common causative microorganism responsible for UTIs (7,19). However, the resistance pattern of E. coli to antibiotics has been very different in various studies.…”
Section: Discussionmentioning
confidence: 96%
“…In recent reports carried out in Iraq, it was found that E. coli, Staphylococcus spp., and K. pneumonia were the most common infectious agents causing UTI, which were also resistant to the most commonly used antibiotics (6,7).…”
Section: Introductionmentioning
confidence: 99%